What should regulators do about merger policy? - Kashyap, Anil K (Journal of Banking & Finance, 1999)
I argue that merger policy needs to be driven by different considerations in Europe, Japan and the United States. In Europe the main challenge is to set up a system so that efficient consolidation can occur once the single currency is established. In Japan the policy ought to be directed towards trying to attract foreign institutions to acquire under-capitalized domestic institutions. Japan does not seem to be taking this route. In the US consolidation it is already occurring and the current policy should be continued.